Literature Review: Diagnosis, Classification, Clinical Manifestations, Pathophysiology, and Treatment of Diabetic Neuropathy - Halim, Susanna; Rajagukguk, David (Journal of Science and Science Education, 2025)
Diabetic neuropathy (DN) is a very common and debilitating complication of Diabetes Mellitus disease that greatly affects quality of life. The literature review aims to critically summarize recent findings that examine the development of understanding of DN, from a simple complication to a complex and multifaceted disease. This study used a literature review based on articles obtained from Google Scholar and PubMed databases. All articles discussed Diabetic Neuropathy from the perspective of pathophysiology, clinical classification, diagnosis, and management. The analysis was conducted using a descriptive-qualitative approach, reported pharmacological and non-pharmacological therapy options. Based on the search, all articles that met the inclusion criteria were narrative reviews, consensus studies, and case reports. These articles outlined the complexities of Diabetic Neuropathy diagnosis, evolving pathophysiological theories, and therapeutic approaches. A multidisciplinary diagnostic approach that includes a thorough history, neurological clinical examination, and ancillary tests (e.g., HbA1c, MRI) is essential. Management involves pharmacological therapy (e.g., tricyclic antidepressants, gabapentinoid), non-pharmacological therapy (e.g., cognitive behavioral therapy, nerve blocks), and comprehensive oral health management. Interdisciplinary collaboration between clinicians, neurologists, and endocrinologists is essential for optimal patient care. Further research is needed to understand the detailed mechanisms and develop more effective therapies